SUPPLEMENTARY MATERIALS WITH THE LOCAL STORIES FOR EXTENSIVE READING ACTIVITY FOR THE NINTH GRADE OF SMP - Dilla, Nora (Jurnal Pembelajaran Prospektif, 2019)
This study aims at developing supplementary reading materials with local values of Sukadana for extensive reading activity designed for the ninth grades students of SMPN 1 Sukadana. Using research and development model adapted from Hyland (2003) and stages of materials development model adapted from Tomlinson (2012) as the bedrock of the study, supplementary reading materials containing four local stories is produced. The pictures and illustrations laid were able to assist the students in understanding the texts and also to attract them to read. The students are expected to use this product as additional materials for extensive reading activity since such materials are not available in their school library and in the market. In addition, teachers can implement Extensive Reading activity by utilizing this product since it can help the students to read more fluently and to expand their knowledge.